Ultrasonic optic nerve sheath diameter could improve the prognosis of acute ischemic stroke in the intensive care unit - Li, Cong; Wang, Cui-Cui; Meng, Yan; Fan, Jia-Yu; Zhang, Jie; Wang, Li-Juan (Frontiers in Pharmacology, 2022)
Objectives: Stroke patients with high intracranial pressure (ICP) may have poor prognosis. Noninvasive ultrasonic optic nerve sheath diameter (ONSD) could evaluate increased ICP. To investigate whether ONSD is valuable for prognosis of patients with acute ischemic stroke (AIS). Methods: AIS receiving intensive care were recruited with the Glasgow Coma Scale (GCS) score. Patients in group A underwent ultrasonic ONSD to assess ICP voluntarily, whereas group B without ONSD. Patients were followed up at discharge and once a week for 3 months with Glasgow Outcome Scale (GOS) score (4–5 scores indicated good prognosis and 1–3 scores indicated poor prognosis). Results: Forty-nine patients were included. GCS scores did not differ significantly between groups A (26 patients) and B (8±3 vs. 7±3, P < 0.05). In group A, ONSD was 5.01±0.48 mm, which correlated with GCS score (P＜0.05). At discharge, the GOS score was higher in group A than in group B (3.35±1.35 vs. 2.57±1.121, P＝0.034). The proportion of patients with a good prognosis was higher in group A than in group B (46.2% vs. 13.0%, P = 0.006). At discharge and after 3 months of follow-up, ONSD at admission was correlated with the GOS score in group A (r = -0.648 [P<0.05] and -0.731 [P<0.05], respectively). After 3 months of follow-up, the GOS score was higher in group A than group B (3.00±1.673 vs. 2.04±1.430, P＜0.05). The proportion of patients with a good prognosis was higher in group A than in group B (46.2% vs. 21.2%, P = 0.039). The Kaplan-Meier curve showed a higher rate of good prognosis in group A than in group B. ONSD (P < 0.05) was an independent predictor of poor prognosis. Conclusion: Noninvasive ultrasonic ONSD could be useful in improving the prognosis of patients with AIS receiving intensive care.